Polypharmacy and potentially inappropriate medication (PIM) use among older veterans with idiopathic pulmonary fibrosis (IPF) – a retrospective cohort study - Daniel M. Guidot; Marc Pepin; S. Nicole Hastings; Robert Tighe; Kenneth Schmader (BMC Pulmonary Medicine)
Abstract Background Idiopathic pulmonary fibrosis (IPF) is a deadly respiratory disease of older patients. IPF therapies (antifibrotics) are efficacious in slowing disease progression, but they are critically underutilized. Potential barriers to antifibrotic use are polypharmacy and potentially inappropriate medications (PIM). We examined the frequency of these factors for older patients with IPF. Methods We retrospectively analyzed records of Veterans ≥ 65 years old in the Durham Veterans Affairs Health Care System who received a diagnosis of IPF and received care between 11 April 2023 and 9 September 2024. We analyzed medication profiles from the Corporate Data Warehouse including total medication counts, polypharmacy (≥ 5 medications), severe polypharmacy (> 15 medications), and prescription of a PIM in the anticholinergic, antidepressant, sedative, and antipsychotic classes using published geriatric guidelines (2023 Beers criteria, Screening Tool of Older People’s Potentially Inappropriate Prescriptions [STOPP] version 3). Identified PIMs underwent protocolized review to categorize them further as likely appropriate or inappropriate. Results We identified 367 Veterans ≥ 65 years old with a diagnosis of IPF diagnostic during our study period. Total medication count was high for older Veterans (mean 14.2, SD 7.0). Veterans commonly had polypharmacy (350/367, 95.4%), severe polypharmacy (161/367, 43.9%), and ≥ 1 PIM (97/367, 26.4%). After protocolized review, 5.7% (21/367) of older Veterans with IPF had a likely inappropriate medication without documentation of a failed preferred alternative. Conclusion For older Veterans with IPF, polypharmacy and PIM use were common and represent likely barriers to effective IPF pharmacotherapy initiation. Interventions that target these factors like deprescribing could improve antifibrotic use. Clinical trial number Not applicable.